Avaliação da fertilidade de solos de Viçosa, Minas Gerais; uso de microparcelas - Mário Braga, José (Revista Ceres, 2025)
This paper reports results obtained with the instalation of the corn micro-plots method in order to evaluate soil fertility in Viçosa; obtain data that may relate wet weight and dry weight; study maximum values that can be added to soils in order do reach the limit of sline concentration and study the possibility of using the method in correlation studies with chemical analysis of soil.